Analysis of Factors Relating to Community Compliance with the Implementation of Health Protocols Post Covid-19 Vaccination - Juita Epelina Sinambela; Daniel Ginting; Taruli Rohana Sinaga (Jurnal Ilmiah Kesehatan (JIKA), 2022)
The implementation of health protocols in the community has decreased after the decline in Covid-19 cases globally, especially in Indonesia. People assume that they will be immune to the virus after being vaccinated, and the President's discourse that people can already take off their masks outside the room, resulting in decreased public compliance in implementing health protocols. This study aimed to analyze factors related to community compliance in implementing the Covid-19 post-vaccination health protocol at the Matiti Health Center, Humbang Hasundutan Regency in 2022. The cross-sectional method was used in the study design. Data collection was in the form of primary data by giving questionnaires to the public who visited the Maititi Health Center with a total sample of 237 people using accidental sampling. The results of the bivariate analysis show that the variables age, education, knowledge, attitudes and availability of Covid-19 prevention facilities and infrastructure are related to community compliance in implementing health protocols after Covid-19 vaccination. It can be concluded that the dominant variables related to community compliance in implementing the post-vaccination Covid-19 health protocol are education and the availability of Covid-19 prevention facilities and infrastructure.